Um sistema autônomo para navegação de cadeiras de rodas robóticas orientadas a pessoas com deficiência motora severa - Celeste, Wanderley Cardoso (2009)
This dissertation proposes a solution to the problem met by people with severe motordiseases, which have full incapacity of moving around by themselves, but keep intact their cognitive abilities. Such a solution is a navigating system for a Robotic Wheelchair, which consists of a control system, a reference generating system and a supervisory system. The control system comprises a set of kinematic controllers to execute speci c tasks, besides a dynamic compensation controller capable to adapt itself in the presence of structured uncertainties and being robust to unstructured uncertainties. The robust adaptive dynamic compensator is based on a dynamic model of the robotic wheelchair carrying a user seated. Speci c tasks are accomplished by the reference generator based on a user command and vehicle information. User commands establish poses of interest to be reached by the robotic wheelchair after following a safe route. To split a general task in speci c ones is the strategy here adopted to reduce the complexity of the navigating system, which should also take care of the safety and comfort of the user. The supervisory system is responsible for an adequate coordination of the kinematic controllers, in addition to perform a sequence of speci c tasks. Simulation and experimentation results show the good performance of the system, even when submitted to changes caused by a user on board the vehicle and by external e ects.